PENGARUH EKSTRAK BAWANG PUTIH TUNGGAL (Allium sativum) TERHADAP LAJU RESPIRASI MENCIT JANTAN DIET TINGGI LEMAK - Ilda Sartifa Sari; Sri Rahayu Lestari; Murni Sapta Sari (Universitas Negeri Malang, 2017)
The aim of this research was to find effect single garlic extract on the respiratory rate of HFD model mice. The experimental animals were 2-month-old Balb-C mice with an average initial body weight of ±18-34g. Mice were divided into two groups that were given a standard diet (normal) and a high-fat diet. Mice were given HFD for 45 days, then treated with a single garlic extract (EBT) with successive treatment HFD + 100mg / KgBB, HFD + EBT200mg / KgBB, and HFD + EBT400mg / KgBB given for 37 days or 5 weeks. Respiration rate measurements were carried out at the 3rd week using a simply assembled respirometer. There are three parameters in this measurement, that is weight, a maximum result time, and respiration rate. There are three parameters in this measurement, namely weight, maximum acquisition time, and respiration rate. This research data is in the form of quantitative data and analyzed using one-way ANOVA test. The results showed that there was no significant effect on the respiration rate of male mice in the high-fat diet model.